2011
DOI: 10.1002/jnr.22602
|View full text |Cite
|
Sign up to set email alerts
|

Ion channel blockers and spinal cord injury

Abstract: The activation of a delayed secondary cascade of unsatisfactory cellular and molecular responses after a primary mechanical insult to the spinal cord causes the progressive degeneration of this structure. Disturbance of ionic homeostasis is part of the secondary injury process and plays an integral role in the early stage of spinal cord injury (SCI). The secondary pathology of SCI is complex and involves disturbance of the homeostasis of K(+) , Na(+) , and Ca(2+) . The effect of ion channel blockers on chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 110 publications
0
31
0
Order By: Relevance
“…Tetrodotoxin (TTX) is a low-molecular-weight guanidine neurotoxin that acts as a specific blocker of voltage-gated sodium (NaV) channel [17]. TTX has neuroprotective properties by blocking NaV channels, preventing neuronal death by diminishing depolarization, cellular Na + /Ca +2 exchange, and neuronal glutamate release [18].…”
Section: Tetrodotoxinmentioning
confidence: 99%
See 1 more Smart Citation
“…Tetrodotoxin (TTX) is a low-molecular-weight guanidine neurotoxin that acts as a specific blocker of voltage-gated sodium (NaV) channel [17]. TTX has neuroprotective properties by blocking NaV channels, preventing neuronal death by diminishing depolarization, cellular Na + /Ca +2 exchange, and neuronal glutamate release [18].…”
Section: Tetrodotoxinmentioning
confidence: 99%
“…The beneficial effects of TTX in preclinical studies include a reduction of white matter loss after SCI [17][18][19], promoting a motor function restoration. The effect of TTX is time-dependent [20].…”
Section: Tetrodotoxinmentioning
confidence: 99%
“…Afterwards, the secondary neurodegenerative events start and worsen the initial injury. Excessive accumulation of intracellular calcium is a common phenomenon after SCI and it is the most critical step in ionic dysregulation that generates axonal injury and eventual apoptosis or necrosis via an increase in cellular enzymes activation, mitochondrial damage, acidosis, and free radicals production [4-9]. …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important to gain an understanding of the pathophysiology underlying SCI in order to develop clinical treatment strategies (1,2). Typically, there are two phases of SCI; the primary injury, in which mechanical impact is afflicted directly on the spine, and the secondary injury, which involves a complex cascade of molecular events, including disturbances in ionic homeostasis (3), local edema, vascular abnormalities, ischemia-reperfusion, glutamate excitotoxicity and inflammatory responses (46). Previous studies have indicated that, following SCI, stress responses of the endoplasmic reticulum (ER) drive neurons and oligodendrocytes towards apoptosis (7).…”
Section: Introductionmentioning
confidence: 99%